2019
DOI: 10.1108/inmr-11-2018-0085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of business models innovation – a multiple case study

Abstract: Purpose -This paper aims to analyze the business model innovation in medium and large Brazilian manufacturing companies located in Rio do Sul State.Design/methodology/approach -A holistic multiple case study in five companies was developed. Data were collected through interviews and analyzed according to the content analysis technique.Findings -The main motivation to business model innovation was the innovation in products and services, while the difficulties were the factors relating to the cost. The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This shows that BMI applies to startups and established companies, and highlights the difference between the design of a business model (Sushandoyo et al, 2020) and its fast reconfiguration, recombination (Priyono et al, 2020) or a new configuration (Nunes & Russo, 2019), to overcome the crisis by choosing less uncertain and costly measures (Massa & Tucci, 2014;Amit & Zott, 2015). Therefore, unicorns indicate how adaptable they are to the current scenario, showing competencies for quickly reconfiguring their business model, skills to attract investments and adopt incremental innovations, combining innovations in various dimensions that represent the BMI (Nunes & Russo, 2019). Some characteristics stand out in the analyzed companies that allowed digital and incremental BMIs: high capacity to manage and transact costs through technologies (Company A), ability to finance its own solutions (Company D), high capacity to increase digital innovations (Company B), long-term entrepreneurial vision (Company C) and strategic investments (Company E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that BMI applies to startups and established companies, and highlights the difference between the design of a business model (Sushandoyo et al, 2020) and its fast reconfiguration, recombination (Priyono et al, 2020) or a new configuration (Nunes & Russo, 2019), to overcome the crisis by choosing less uncertain and costly measures (Massa & Tucci, 2014;Amit & Zott, 2015). Therefore, unicorns indicate how adaptable they are to the current scenario, showing competencies for quickly reconfiguring their business model, skills to attract investments and adopt incremental innovations, combining innovations in various dimensions that represent the BMI (Nunes & Russo, 2019). Some characteristics stand out in the analyzed companies that allowed digital and incremental BMIs: high capacity to manage and transact costs through technologies (Company A), ability to finance its own solutions (Company D), high capacity to increase digital innovations (Company B), long-term entrepreneurial vision (Company C) and strategic investments (Company E).…”
Section: Discussionmentioning
confidence: 99%
“…Despite great digital mobility, flexibility, capacity to allocate assets promptly, competence to innovate quickly and ability to attract different forms of investments (De Massis, Frattini, & Quillico, 2016; Hogarth, 2017), unicorns also face challenges that can be seen as new opportunities and learning (Dalmarco, Maehler, Trevisan, & Schiavini, 2017). They foster managers to act differently, by innovating their business models (Nunes & Russo, 2019) and putting into practice new measures to create value for customers (Kuckertz et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Various enterprise factors are associated with innovation in an organization such as the professional development, employee initiatives, and inclusion in decision-making process. In the literature (Nunes and Russo, 2019), the researchers evaluated innovative business models among the large and medium scale manufacturing companies in Brazil. In this multiple case study-based research work, the researchers found that the most common innovation occurs in value proposition and learning-by-searching is the most extensively utilized method of innovation.…”
Section: Small- Medium- and Large-sized Enterprisesmentioning
confidence: 99%
“…New business models are likely to provide new opportunities to address customer needs better, generating differentiation from its competitors (Nunes & Russo, 2019). A business model is a conceptual tool containing a set of concepts and relationships to express a specific firm's business logic.…”
Section: Business Modelmentioning
confidence: 99%